2021
DOI: 10.1002/1878-0261.13050
|View full text |Cite
|
Sign up to set email alerts
|

EHMT1 knockdown induces apoptosis and cell cycle arrest in lung cancer cells by increasing CDKN1A expression

Abstract: Dozens of histone methyltransferases have been identified and biochemically characterized, but the pathological roles of their dysfunction in human diseases such as cancer remain largely unclear. Here, we demonstrate the involvement of EHMT1, a histone lysine methyltransferase, in lung cancer. Immunohistochemical analysis indicated that the expression levels of EHMT1 are significantly elevated in human lung carcinomas compared with non-neoplastic lung tissues. Through gene ontology analysis of RNA-seq results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…Several papers have reported that the upregulation of CDKN1A induces cell cycle arrest and apoptosis in cancer cells and normal cells [17][18][19][20][21]. Additionally, our team reported that the upregulation of CDKN1A by PRMT1 and EHMT1 knockdown induced cell apoptosis in hepatocellular carcinoma and lung cancer [22,23]. Thus, we clearly observed the upregulation of CDKN1A expression at the transcriptional level after EHMT2 knockdown.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Several papers have reported that the upregulation of CDKN1A induces cell cycle arrest and apoptosis in cancer cells and normal cells [17][18][19][20][21]. Additionally, our team reported that the upregulation of CDKN1A by PRMT1 and EHMT1 knockdown induced cell apoptosis in hepatocellular carcinoma and lung cancer [22,23]. Thus, we clearly observed the upregulation of CDKN1A expression at the transcriptional level after EHMT2 knockdown.…”
Section: Discussionsupporting
confidence: 67%
“…In a previous study, we also reported that EHMT1 knockdown induced CDKN1A expression and cell apoptosis via G1 arrest in lung cancer [23]. Because EHMT1 and EHMT2 form heterodimers to perform H3K9 methylation, thereby suppressing gene expression in various cancers, we predicted that EHMT1 may be related to CDKN1A expression in colon cancer, as shown by EHMT2-related CDKN1A regulation.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, several studies have indicated that overexpression of EHMT1 is observed in several types of cancer, including breast cancer, gastric cancer, and esophageal squamous cell cancer, suggesting that EHMT1 is related to tumor development and metastasis progression (Cebrian et al, 2006;Guan et al, 2014;Yang et al, 2018). In a previous study, we also overexpressed EHMT1 and confirmed that EHMT1 directly regulates CDKN1A in lung cancer, causing cell cycle arrest and inducing apoptosis (Lee et al, 2021). However, in CRC, the function of EHMT1 is not fully understood.…”
Section: Introductionsupporting
confidence: 67%
“…In a previous study, we reported that EHMT1 regulates CDKN1A gene expression through epigenetic regulation and consequently plays a critical role in the regulation of lung cancer cell apoptosis and the cell cycle ( Lee et al, 2021 ). Therefore, we expected that EHMT1 would affect cell cycle regulation in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cdkn1a is associated with p53/TP53-mediated inhibition of cellular proliferation in response to DNA damage. Cdkn1a regulates cell cycle progression, terminal differentiation, and apoptosis [ [67] , [68] , [69] ]. Chac1 catalyzes the cleavage of glutathione and is known as a pro-apoptotic component associated with oxidative stress and apoptosis pathways [ [70] , [71] , [72] ].…”
Section: Discussionmentioning
confidence: 99%